2021
DOI: 10.33102/uij.vol33no3.362
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Online Problem-Based Learning Methods on Students’ Performance

Abstract: The COVID-19 pandemic has a significant impact on the education process in higher education institutions. The medical faculty is forced to adapt by implementing distance learning. The entire face-to-face learning is replaced with virtual meetings to prevent transmission of the COVID-19 virus. Problem-based learning (PBL) is carried out online. This study aimed to analyse students' performance during an online PBL in terms of their content knowledge about the modules. The study was conducted in the 2019/2020 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Students indicated that they improved their critical thinking and independent research skills, while the academic staff amplified the students' acquisition of critical analysis and communication skills. These findings are reinforced by research that has shown that the online PBL approach enhances interpersonal, communication and collaboration skills 3,29,38 ; and supports access to information and collaborative learning among students 43 . Skills that are core to achieving health promotion competencies 12 translating to the workplace upon graduation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Students indicated that they improved their critical thinking and independent research skills, while the academic staff amplified the students' acquisition of critical analysis and communication skills. These findings are reinforced by research that has shown that the online PBL approach enhances interpersonal, communication and collaboration skills 3,29,38 ; and supports access to information and collaborative learning among students 43 . Skills that are core to achieving health promotion competencies 12 translating to the workplace upon graduation.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are reinforced by research that has shown that the online PBL approach enhances interpersonal, communication and collaboration skills 3 , 29 , 38 ; and supports access to information and collaborative learning among students. 43 Skills that are core to achieving health promotion competencies 12 translating to the workplace upon graduation. These were key outcomes we hoped to impart in our student cohort with each iteration of the PBL approach.…”
Section: Discussionmentioning
confidence: 99%